The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41584-019-0240-8
|View full text |Cite
|
Sign up to set email alerts
|

Stratifying management of rheumatic disease for pregnancy and breastfeeding

Abstract: The management of inflammatory rheumatic diseases during pregnancy and breastfeeding has undergone considerable change in the past few years. Modern therapeutics, including biologic and targeted synthetic DMARDs, have enabled substantial improvements in control of rheumatic diseases, resulting in more patients with severe disease considering pregnancy. Therefore, management of disease for these patients needs to be discussed with clinicians before, during and after pregnancy and patients need to know what comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 140 publications
(228 reference statements)
0
31
0
8
Order By: Relevance
“…The advent of biologic agents has changed the way we treat rheumatic conditions but these come with their own risks. Maternal IgG alone is a large protein that cannot diffuse passively across the placenta [8]. Maternal IgG is actively transferred across the placenta via the neonatal FC receptor [17].…”
Section: Immunizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of biologic agents has changed the way we treat rheumatic conditions but these come with their own risks. Maternal IgG alone is a large protein that cannot diffuse passively across the placenta [8]. Maternal IgG is actively transferred across the placenta via the neonatal FC receptor [17].…”
Section: Immunizationsmentioning
confidence: 99%
“…The transfer occurs from week 20 of the second trimester. Certain biologic agents contain IgG1 proteins and therefore are also actively transported across the placenta via the neontatal FC receptor from week 20 [8,16]. This results in the baby being exposed to the biologic agent.…”
Section: Immunizationsmentioning
confidence: 99%
“…Although inconclusive, nulliparity and short-duration breastfeeding have been suggested as risk factors for female RA development [5,6]. In addition, several studies have shown that a substantial number of pregnant patients with RA experience clinical remission, but disease ares frequently occur during the postpartum period [7,8]. Thus, experiences during the course of RA may differ between men and women.…”
Section: Introductionmentioning
confidence: 99%
“…RDs during pregnancy are associated with adverse maternal and fetal outcomes, 2 and therapy discontinuation prompts a disease flare. Disease activity control during pregnancy is crucial for optimal obstetric management 2 .…”
mentioning
confidence: 99%
“…RDs during pregnancy are associated with adverse maternal and fetal outcomes, 2 and therapy discontinuation prompts a disease flare. Disease activity control during pregnancy is crucial for optimal obstetric management 2 . Interestingly, tumor necrosis factor alpha (TNF‐a), interleukin‐1 (IL‐1), and interleukin‐6 (IL‐6), which are produced in response to infections (such as COVID‐19) and tissue injuries (such as RDs), 3 are considered key cytokines for pathophysiology in the aforementioned diseases.…”
mentioning
confidence: 99%